PENYELESAIAN POTENSI KONFLIK KEPENTINGAN MASYARAKAT KABUPATEN KOLAKA TIMUR DENGAN TAMAN NASIONAL RAWA AOPA WATUMOHAI PROVINSI SULAWESI TENGGARA - Hasbullah Syaf; La Baco Sudia; Baso Mursidi; Asramid Yasin (Journal Publicuho, 2022)
The Rawa Aopa Watumohai National Park area (TNRAW) is an administrative area of East Kolaka Regency and is in direct contact with the TNRAW area, so community activities to use TNRAW as business land cannot be stopped. This study aims to analyze potential TNRAW conflicts and provide direction for problem resolution. This study combined the survey method with a participatory approach with the community and TNRAW managers. The results showed several problems encountered in villages included in the TNRAW area, including encroachment and illegal logging, land sale and purchase, land certification, settlements within the area, plantations within the area, rice fields in the area, construction of facilities and infrastructure by the government, recognition of village administration in the area, allocation of village funds and waterlogging and overfishing. Community stakeholder actors have a negative influence or role in the TNRAW area. The role of the Southeast Sulawesi Provincial Public Works Office, Universities, Non-Governmental Organizations (NGOs), and the Ministry of Environment and Forestry (KLHK) as stakeholder actors is positive for both the community and TNRAW. Recommendations for problem resolution directives include: 1) increasing community participation through continuous empowerment and assistance so that adverse roles of TNRAW can be minimized, 2) increasing the role of stakeholders to coordinate with TNRAW, especially concerning land legality and community agricultural activities within the TNRAW Area, 3) solving various problems in TNRAW through mutually beneficial mechanisms between the community and TNRAW, The solutions offered must, of course, be following applicable laws and regulations.